Understanding Debt Dynamics: The Role of Financial Literacy, Income, and Lifestyle with Gender as a Moderating Variable - Zulfa Zakiatul Hidayah; Erin Soleha (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to prove the extent to which the relationship between Financial Literacy, Income, and Lifestyle influences Debt Behavior, apart from that, judging from the psychological factors, women and men have different emotions, which is quite an important consideration in moderating debt behavior, so researchers use gender as a moderating variable. This research has a research focus on Social Humanities, Arts and Culture, and Education with the theme of Economics and human resources on the topic of strengthening human resource capacity which focuses on gender justice, social inclusion, and sustainability following applicable guidelines (Kementrian Pendidikan, Kebudayaan, Riset, 2024). The method used in this research is mixed, namely Quantitative and Quantitative (Quan-Qual). The primary data is collected by distributing questionnaires directly and conducting direct interviews with respondents, while secondary data is in the form of scientific articles and other data that are used as references. The population in this research is all people in the province of West Java. Samples were collected using the Accidental Sampling technique, and statistical testing tools using Structural Equation Modeling (SEM) with SmartPLS software. The research results show that financial literacy, lifestyle, and gender directly influence investment behavior, while income has no impact. Indirectly, financial literacy, income, and lifestyle moderated by gender do not influence investment behavior, meaning that neither men nor women have any influence.